2019
DOI: 10.1074/jbc.ra118.005408
|View full text |Cite
|
Sign up to set email alerts
|

Phenamacril is a reversible and noncompetitive inhibitor of Fusarium class I myosin

Abstract: Edited by Velia M. FowlerThe cyanoacrylate compound phenamacril (also known as JS399 -19) is a recently identified fungicide that exerts its antifungal effect on susceptible Fusarium species by inhibiting the ATPase activity of their myosin class I motor domains. Although much is known about the antifungal spectrum of phenamacril, the exact mechanism behind the phenamacril-mediated inhibition remains to be resolved. Here, we describe the characterization of the effect of phenamacril on purified myosin motor co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 54 publications
5
24
0
Order By: Relevance
“…These compounds have been developed to inhibit mammalian myosins. In contrast, phenamacril is the only reported inhibitor that is specific for some plant pathogens [4,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These compounds have been developed to inhibit mammalian myosins. In contrast, phenamacril is the only reported inhibitor that is specific for some plant pathogens [4,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Phenamacril is a novel reversible and non-competitive inhibitor of Fusarium myosin I [27]. All Fusarium species have only a single class I myosin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed that the class I myosin, FgMyoI is the drug target of phenamacril in F. graminearum . Phenamacril directly binds with FgMyo1 and suppresses the ATPase activity of FgMyo1 . In the laboratory, substitution of an amino acid residue in FgMyo1 or its homologs in F. asiaticum and F. fujikuroi leads to high resistance to the fungicide .…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Phenamacril directly binds with FgMyo1 and suppresses the ATPase activity of FgMyo1. 26,28 In the laboratory, substitution of an amino acid residue in FgMyo1 or its homologs in F. asiaticum and F. fujikuroi leads to high resistance to the fungicide. 25,26 Until now, phenamacril resistant strains of F. graminearum have not been found in the field, while resistant strains of F. fujikuroi have existed in the field for some time.…”
Section: Introductionmentioning
confidence: 99%